Cine nuestro. herramienta digital que difunde información sobre el cine independiente colombiano en la ciudad de Bogotá (2019)
Colombian indie movies is an artistic expression that has gain higher value in our country, it due to national and international successful of its feature films and also because there are more and more productors with the initiative to film this kind of movies to value our culture and history. Even though colombian cine has grown, it is darkened due to few resources for this industry. Resources could be enough for the production but are not enough for promotion and movie diffusion. According with the last Proimágenes (2017) report, of 100% of movies spectators, just 6% of them watched a Colombian movies and over this 6% only a 16% watched local featured films. As a consequence, this leave less support, our movies devaluation and also it leave losts for Colombian cinematographic industrie. In this way, the biggest problem of Colombian feature films is the promotion, because if a movie is not promoted, people can’t know about its existence or even if it is in theaters, this provoque that the movie is usually removed from theaters because is not profitable. By identifying the communicative void in relation to the main actors, the viewer and the producer due to the lack of diffusion, a design opportunity is glimpsed. For this reason, the "Cine Nuestro" project proposes the use of a digital tool to open up the possibility of broadcasting Colombian cinematographic contents in the city of Bogotá; This is done through a mixed-type project methodology (quantitative and qualitative data), which addresses the design of services with a focus on user-centered design. It concludes the importance of targeting film viewers who are motivated to see and contribute to the preservation of Colombian independent cinema, through a web page and a media strategy. In this way, "Cine Nuestro" becomes a communication bridge between the user and this type of productions, by providing interesting, attractive and timely information with the purpose of motivating users to see, know and value our cinema